Cohort Effects in the Educational Attainment of Second Generation Immigrants in Germany: An Analysis of Census Data - Regina T. Riphahn (Institute for the Study of Labor (IZA), 2001)
Even though second generation immigrants make up ever increasing population shares in industrialized countries we know little about their social integration and wellbeing. This study focuses on the educational attainment of German born children of immigrants. Their schooling success still lags behind that of natives. We investigate completed degrees and school attendance of German born immigrants and find considerable evidence suggesting that this group does not assimilate to native education standards but instead increasingly falls behind.
Keywords: I21; J24; J61; 330; Second generation immigrants; educational attainment; assimilation; Ausländer; Jugendliche; Bildungsverhalten; Bildungsniveau; Soziale Integration; Kohortenanalyse; Schätzung; Deutschland